Structure of amorphous materials in the NASICON system Na1+xTi2SixP3−xO12. (12th July 2023) - Mendes Da Silva, Rita; Zeidler, Anita; Bradtmüller, Henrik; Eckert, Hellmut; Fischer, Henry E; Benmore, Chris J; Salmon, Philip S
Abstract: The structure of glasses in the sodium (Na) super-ionic conductor (NASICON) system Na 1 + x Ti2 Si x P 3 − x O12 with x = 0.8 and x = 1.0 was explored by combining neutron and high-energy x-ray diffraction with 29 Si, 31 P and 23 Na solid-state nuclear magnetic resonance (NMR) spectroscopy. The 29 Si magic angle spinning (MAS) NMR spectra reveal that the silica component remains fully polymerized in the form of Si 4 units, i.e. the silicon atoms are bound to four bridging oxygen atoms. The 31 P{ 23 Na} rotational echo adiabatic passage double resonance (REAPDOR) NMR data suggest that the 31 P MAS NMR line shape originates from four-coordinated P n units, where n = 1, 2 or 3 is the number of bridging oxygen atoms per phosphorus atom. These sites differ in their 31 P- 23 Na dipolar coupling strengths. The results support an intermediate range order scenario of a phosphosilicate mixed network-former glass in which the phosphate groups selectively attract the Na + modifier ions. Titanium takes a sub-octahedral coordination environment with a mean Ti–O coordination number of 5.17(4) for x = 0.8 and 4.86(4) for x = 1.0. A mismatch between the P–O and Si–O bond lengths of 8% is likely to inhibit the incorporation of silicon into the phosphorus sites of the NASICON crystal structure.